2021
DOI: 10.2478/aoas-2020-0053
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Incubation and Turning During Long Storage as a Method of Improving Hatchability and Chick Quality of Japanese Quail Eggs

Abstract: In this study, we investigated the effect of modification of 12 d storage conditions of quail eggs from two flocks: at 17–20 weeks of life (A) and 36–39 weeks of life (B) on the incubation time, hatch window (HW), hatching results and chicks quality. The eggs were divided into experimental groups: COI = no pre-incubation (PI); SPIDES = were treated with 4 h PI, delivered at 4, 6, 8 and 10 d of storage; EG SPIDES = were treated with variable time of PI according to the scheme 5 d – 2 h, 7 d – 3 h, 9 d – 5 h and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
3
5
0
Order By: Relevance
“…In the current study, eggs treated by SPIDES recorded a short average of hatch time, the time it took for 90% of the eggs to hatch, the mean hatching time, and the maximal hatching period, and the first chicks were recorded in 480 h of incubation. The outcomes are consistent with those of Damaziak et al ( 2018 ) and Damaziak et al ( 2021 ) who stated that the first chicks were observed in the first SPIDES group after 477 h and in the second SPIDES group after 479 h. However, the hatching window for the first SPIDES group was relatively long, lasting up to 21 h, whereas it was only 13 h long for the second SPIDES group. Longer egg holding duration was found in the research done by Dymond et al ( 2013 ) and Nasri et al ( 2017 ), and this may be the reason even in the “SPIDES” group, the scientists were able to extend the incubation period by a significant amount: 499–508 h. Also, after 21 days of cold storage, they were able to reduce the pre-incubation heating time to 6 or 12 h. Reijrink et al ( 2010 ) also found a decrease in incubation time utilizing 24 h (PI) throughout 14 days of cold storage.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In the current study, eggs treated by SPIDES recorded a short average of hatch time, the time it took for 90% of the eggs to hatch, the mean hatching time, and the maximal hatching period, and the first chicks were recorded in 480 h of incubation. The outcomes are consistent with those of Damaziak et al ( 2018 ) and Damaziak et al ( 2021 ) who stated that the first chicks were observed in the first SPIDES group after 477 h and in the second SPIDES group after 479 h. However, the hatching window for the first SPIDES group was relatively long, lasting up to 21 h, whereas it was only 13 h long for the second SPIDES group. Longer egg holding duration was found in the research done by Dymond et al ( 2013 ) and Nasri et al ( 2017 ), and this may be the reason even in the “SPIDES” group, the scientists were able to extend the incubation period by a significant amount: 499–508 h. Also, after 21 days of cold storage, they were able to reduce the pre-incubation heating time to 6 or 12 h. Reijrink et al ( 2010 ) also found a decrease in incubation time utilizing 24 h (PI) throughout 14 days of cold storage.…”
Section: Resultssupporting
confidence: 91%
“…Eggs saved for 5 days had a higher percentage of hatchability than eggs kept for 15 days. The outcomes are in line with those of Damaziak et al ( 2021 ); Pokhrel et al ( 2018 ) discovered that hatchability was shown to be greater after 7 days of storage compared to when it was at 0 days, and it decreased with longer storage intervals (21 to 28 days). This may be due to long-term storage, which raises albumen pH and lowers albumen elevation and thickness.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The improved hatchability % following the frequent short bursts of SPIDES agreed with the results of Maman and Yildirim [28], Ozlu et al [27], Silva et al [31], and Tag EL-Din et al [32] who noted that short periods of incubation for 6 h before the storing for 14 days improved the hatchability % due to lowering late embryonic mortality. Moreover, our obtained results were in line with the results of Damaziak et al [33] which reported that eggs stored for 7 days had higher hatchability % than freshly laid eggs and prolonged stored ones for 21 to 28 days. This effect may be correlated with in sufficient O 2 levels for early chick embryo's metabolic demands [34] and due to increasing albumen pH with the prolonged storage, respectively.…”
Section: Effect Of Storage Period Frequent Spides and Chicken Breed O...supporting
confidence: 92%
“…Incubation is a critical stage in the poultry production system, and its efficiency is dependent on various environmental factors. Notably, the storage period of fertile eggs plays a major role, especially as the industry increasingly faces challenges with the capacity of incubation unable to keep up with the growing number of chicks, leading to extended egg storage (Damaziak et al, 2021). Prolonged storage can compromise chick quality and hatchability rates (Ayeni et al, 2020).…”
Section: Introductionmentioning
confidence: 99%